Fishing for Answers: An exploration of fisherwomen’s roles and activities in the ‘blue economy’ of the South African small-scale fisheries sector - Minnaar, Natasha Daniela (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.